1963
DOI: 10.3133/pp372f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought in the Colorado River basin: Chapter F in <i>Drought in the Southwest, 1942-56</i>

Abstract: The prolonged drought of 1942-56 affected chiefly the lower part of the Colorado River basin and did not extend into the upper basin (the chief water-producing area) until1953. Areas served by the Colorado River had adequate water supplies in spite of the local deficiency of precipitation. In the Gila River basin, there was a deficiency of streamflow during the drought years, and the water requirements of the present population exceed the yield of the basin even during years of average precipitation; the defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…15 of 21 followed in the early 1940s by widespread sediment aggradation and floodplain formation as channels stabilized throughout the basin (Hereford, 1987), likely influenced by low peak flows and below-normal average precipitation that occurred in the 1940s and 1950s (Gellis et al, 1991;Hereford, 1984). Such widespread sediment storage in the basin was coincident with decreases in suspended sediment observed at the CR-Cisco, the GR-Green River UT, and the SJ-Bluff sites (Gellis et al, 1991), as well as decreased salt loading observed throughout the UCRB (Kircher et al, 1984;Moody & Mueller, 1984;Thomas et al, 1963). Strong correlation between sediment and dissolved-solids concentrations has been observed in surface runoff in certain areas of the UCRB, demonstrating that soil erosion, sediment yield, and salinity transport processes can be highly related (Cadaret et al, 2016).…”
Section: Dissolved-solids Trends In the Context Of Ucrb Changementioning
confidence: 99%
“…15 of 21 followed in the early 1940s by widespread sediment aggradation and floodplain formation as channels stabilized throughout the basin (Hereford, 1987), likely influenced by low peak flows and below-normal average precipitation that occurred in the 1940s and 1950s (Gellis et al, 1991;Hereford, 1984). Such widespread sediment storage in the basin was coincident with decreases in suspended sediment observed at the CR-Cisco, the GR-Green River UT, and the SJ-Bluff sites (Gellis et al, 1991), as well as decreased salt loading observed throughout the UCRB (Kircher et al, 1984;Moody & Mueller, 1984;Thomas et al, 1963). Strong correlation between sediment and dissolved-solids concentrations has been observed in surface runoff in certain areas of the UCRB, demonstrating that soil erosion, sediment yield, and salinity transport processes can be highly related (Cadaret et al, 2016).…”
Section: Dissolved-solids Trends In the Context Of Ucrb Changementioning
confidence: 99%